The factors affecting national examination achievement in high schools - Nenden Susilowati; Sukidjo Sukidjo (Harmoni Sosial: Jurnal Pendidikan IPS, 2020)
This research aims to reveal the factors affecting the achievement in the national examination. This study was analytical research. The population in this study totaled 2,243, whereas the amount of the specified sample was 339 students with techniques of stratified random sampling. The population in this study totaled 2, 243, whereas the amount of the specified samples of 339 students with techniques of stratified random sampling. The data collected through a questionnaire, observation, and documentation. The data analysis used the multiple regression model. The research results are as follows. Significant; 1.) There is a significant correlation between the intake of students on the national exam results. The value is of R is 0.740; 2.) There is a significant correlation between the learning motivation of students on the national exam results. The value of R is 0.406; 3.) There, significant is significant. Correlation of the competency of teachers on the National exam results; the value of R is 0.398; 4.) There is a significant correlation of the school environment on the national exam results; the value of R is 0. 366; 5) There is a significant correlation of the family support on the national is exam results; the value of R is 0.443; and 6) There is a significant correlation of the intake of students' learning motivation, the competence of teachers, school environment, and family support simultaneously on the national exam is results of the results; the value of R is 0.825.